2018
DOI: 10.1002/jwmg.21586
|View full text |Cite
|
Sign up to set email alerts
|

Spotted owl foraging patterns following fuels treatments, Sierra Nevada, California

Abstract: Western dry conifer forests continue to experience increased severe, stand-replacing wildfire that is outside of historical precedent. Fuels treatments, landscape-scale modifications of forest fuels and structure, are likely to remain a management tool to modify fire behavior and restore ecological resilience. The impacts of fuels treatments to listed species such as spotted owls (Strix occidentalis) remain uncertain and are contested because of limited available information. To evaluate spotted owl foraging h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Spotted owl nocturnal habitat selection patterns at higher elevations in this study were generally consistent with the results presented in previous studies (Gutiérrez et al 1992, 2017, Irwin et al 2007, Atuo et al 2019, Blakey et al 2019, Gallagher et al 2019). However, habitat selection at lower elevations exhibited a different pattern and was consistent with our hypothesis of elevation‐dependent habitat selection.…”
Section: Discussionsupporting
confidence: 92%
“…Spotted owl nocturnal habitat selection patterns at higher elevations in this study were generally consistent with the results presented in previous studies (Gutiérrez et al 1992, 2017, Irwin et al 2007, Atuo et al 2019, Blakey et al 2019, Gallagher et al 2019). However, habitat selection at lower elevations exhibited a different pattern and was consistent with our hypothesis of elevation‐dependent habitat selection.…”
Section: Discussionsupporting
confidence: 92%
“…First, 2 recent reports on managing the California spotted owl in the Sierra Nevada Forests (Roberts and North , Gutiérrez et al ) cited multiple northern spotted owl papers to describe the potential negative effects of barred owls on spotted owls (Kroll et al ; Dugger et al ; Yackulic et al , ; Wiens et al ). Second, the recovery plan for the Mexican spotted owl (USDI ) cited northern spotted owl and California spotted owl papers on fire effects extensively (Franklin et al , Lee and Irwin , Ager et al , Bond et al , Clark et al ), and extrapolated information on response to forest treatments from studies on the northern spotted owl and the California spotted owl (Meiman et al , Seamans and Gutiérrez , Gallagher , Dugger et al , Stephens et al ). In all cases this extrapolation of information among subspecies was caused by a lack of information specific to the focal subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, for territories in which ≥20 ha of mature coniferous forest was altered, California spotted owls experienced a 2.5% decline in occupancy probability. In the northern Sierra Nevada in eastern California, Gallagher () assessed home range sizes of 8 California spotted owls in areas altered by recent fuels treatments, and reported that home range area increased, a sign of declining habitat quality, as the total area of fuels treatments within the home range increased. These fuels treatments, called defensible fire protection zones (DFPZs), reduced canopy cover, tree density, and ladder fuels.…”
Section: Resultsmentioning
confidence: 99%